Innovative responses to Covid-19: Future pathways for "techvelopment" and innovation - Adam Moe Fejerskov; Dane Fetterer (Danish Institute for International Studies (DIIS), 2020)
Innovation and technology have played a major role in the fight against Covid-19. Localised efforts have proven more robust, low-tech responses more equitable and process innovations more necessary. But there are still long strides to be made in these areas. As development actors pursue these pathways, inequality, data privacy and human rights should remain center-stage in future programming and policy - both during and beyond the pandemic - to ensure an even balance between new innovations and proven strategies and principles for action. These are main findings of a new DIIS study, which explores the impact of Covid-19 on three main areas of concern for development and humanitarian cooperation: 1) sexual and reproductive health and rights and sexual- and gender-based violence, 2) refugees, migrants and IDPs, and 3) food security. Though global infection rates have remained lower for women than for men, the systemic effects on reproductive healthcare and gender-based violence have been profound. For refugees, migrants and IDPs, the economic impact has greatly limited traditional pathways to employment and education. And border closures and supply chain disruptions caused by the pandemic have pushed more vulnerable populations into food insecurity. This DIIS Report is based on the analysis of public health reports, development projects, and interviews with key stakeholders in humanitarian and development organisations working with innovation and technology. It is funded by the Danish Ministry of Foreign Affairs.
Keywords: 300; Coronavirus; Entwicklungspolitik; Innovation; Forschung; Technischer Fortschritt; Entwicklungsländer